Prosecutors, court communities, and policy change: The impact of internal DOJ reforms on federal prosecutorial practices*. Issue 3 (4th July 2021) - Lynch, Mona; Barno, Matt; Omori, Marisa
Abstract: The current study examines how key internal U.S. Department of Justice (DOJ) policy changes have been translated into front‐line prosecutorial practices. Extending courts‐as‐communities scholarship and research on policy implementation practices, we use U.S. Sentencing Commission data from 2004 to 2019 to model outcomes for several measures of prosecutorial discretion in federal drug trafficking cases, including the use of mandatory minimum charges and prosecutor‐endorsed departures, to test the impact of the policy changes on case processing outcomes. We contrast prosecutorial measures with measures that are more impervious to discretionary manipulation, such as criminal history, and those that represent judicial and blended discretion, including judicial departures and final sentence lengths. We find a significant effect of the policy reforms on how prosecutorial tools are used across DOJ policy periods, and we find variation across districts as a function of contextual conditions, consistent with the court communities literature. We also find that a powerful driver of changes in prosecutorial practices during our most recent period is the confirmation of individual Trump‐appointed U.S. Attorneys at the district level, suggesting an important theoretical place for midlevel actors in policy translation and implementation.